Portfolio Within Pedagogic Diagnostics in Primary Schools - Petrová, Jitka; Fasnerová, Martina (Revija za elementarno izobraževanje, 2012)
At the present time, the importance of pedagogic diagnostics at primary school level has been increasing strongly, given the deepening needs to approach every child and every pupil individually. For the above-mentioned reasons, teachers must really search for methods and procedures that will help them understand pupils better in order to be able to support them and help them address certain issues that emerge at school as well as at home. Therefore, portfolio seems to be one of the most suitable tools to get to know a pupils personality in detail since it allows the pupil, the teacher, and the parents to monitor the progress and the development in different fields within longer periods. In spite of that, portfolio has not been widely used in schools and it appears to be a rather marginal tool instead. Therefore, a group from the Pedagogical Faculty of the Palacký University in Olomouc has decided to find out how the concept of portfolio is perceived and accepted by future primary teachers.